2014
DOI: 10.12938/bmfh.33.1
|View full text |Cite
|
Sign up to set email alerts
|

<i>Bifidobacterium breve</i> MCC-117 Induces Tolerance in Porcine Intestinal Epithelial Cells: Study of the Mechanisms Involved in the Immunoregulatory Effect

Abstract: Bifidobacterium breve MCC-117 is able to significantly reduce the expression of inflammatory cytokines in porcine intestinal epithelial (PIE) cells and to improve IL-10 levels in CD4+CD25high Foxp3+ lymphocytes in response to heat-stable enterotoxigenic Escherichia coli (ETEC) pathogen-associated molecular patterns (PAMPs), while the immunoregulatory effect of B. adolescentis ATCC15705 was significantly lower than that observed for the MCC-117 strain. Considering the different capacities of the two bifidobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
4
11
0
1
Order By: Relevance
“…More recently, Finamore et al (2014) signaling in Caco-2/TC7 cells through modulation of the negative regulators Tollip and IRAK-M and, that this effect was dependent on TLR2 signaling. Our previous studies in PIE cells and porcine immune cells also revealed that TLR2 plays an important role in the immunoregulatory activity of immunobiotic bacteria (Shimazu et al, 2012;Tomosada et al, 2013;Villena et al, 2012;Murata et al, 2014). Our studies of the anti-inflammatory activity of L. jensenii TL2937 in PIE cells showed that TLR2 have an important role in the immunoregulatory capacities of this strain.…”
Section: Discussionsupporting
confidence: 60%
“…More recently, Finamore et al (2014) signaling in Caco-2/TC7 cells through modulation of the negative regulators Tollip and IRAK-M and, that this effect was dependent on TLR2 signaling. Our previous studies in PIE cells and porcine immune cells also revealed that TLR2 plays an important role in the immunoregulatory activity of immunobiotic bacteria (Shimazu et al, 2012;Tomosada et al, 2013;Villena et al, 2012;Murata et al, 2014). Our studies of the anti-inflammatory activity of L. jensenii TL2937 in PIE cells showed that TLR2 have an important role in the immunoregulatory capacities of this strain.…”
Section: Discussionsupporting
confidence: 60%
“…Interestingly, the production of cytokines and chemokines in response to ETEC PAMPs by IECs can be modulated with immunobiotic bacteria . In this regard, we have previously demonstrated that L. jensenii TL2937, B. longum BB536, and B. breve MCC‐117 are able to protect PIE cells from ETEC‐mediated inflammatory damage by regulating NF‐κB and MAPK pathways, and suppressing proinflammatory cytokine expression . However, the anti‐inflammatory activity of plant‐derived lactobacilli has been studied to a very limited extent.…”
Section: Discussionmentioning
confidence: 99%
“…Every year, increasing substantial clinical and experimental evidence is reported to support probiotic intervention in immunomodulation . The beneficial effects of immunobiotic LAB have been demonstrated in several in vitro and in vivo studies, which revealed a variety of host effects and generated several hypotheses of the mechanisms by which immunobiotics influence their hosts . Regarding the immunoregulatory effect of immunobiotics, it is now well established that within the gastrointestinal system, probiotics are capable to interact with the host's epithelial‐ and immune cells, and thereby impact epithelial barrier and immune functions .…”
Section: Introductionmentioning
confidence: 99%
“…These strains were shown to activate TLR2 and upregulate some TLR4 negative regulators, as ubiquitin-editing enzyme A20, thus reducing the activation of MAPK and NF-κB pathways and the subsequent production of pro-inflammatory cytokines (Murata et al 2014;Tomosada et al 2013). Another study by the same authors using PIE cells and swine Peyer's patches immunocompetent cell co-culture system showed that the immunoregulatory effect of B.…”
Section: Probiotics Used In Pig Intestinal Cells Challenged With Etecmentioning
confidence: 99%